Multiple Meningiomas in a Child - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The unusual case of a 4-yr, 5-mo-old boy with multiple meningiomas without neurofibromatosis is reported from the Children's Memorial Hospital and Northwestern University Medical School, Chicago, Illinois.